TCRBuilder: multi-state T-cell receptor structure prediction - Wong, WK; Marks, C; Leem, J; Lewis, AP; Shi, J; Deane, CM (Oxford University Press, 2020)
Motivation T-cell receptors (TCRs) are immune proteins that primarily target peptide antigens presented by the major histocompatibility complex. They tend to have lower specificity and affinity than their antibody counterparts, and their binding sites have been shown to adopt multiple conformations, which is potentially an important factor for their polyspecificity. None of the current TCR-modelling tools predict this variability which limits our ability to accurately predict TCR binding.